مشاريع الاستثمار السياحي ودورها في تنشيط الحركة السياحية في ولاية الشلف: Tourism investment projects and their role in revitalizing tourism in the state of Chlef - مناد العالية; راتول محمد (Journal of North African Economies, 2025)
This study aims to determine the relationship between tourism investment and the stimulation of tourism movement in the state of Chlef, by determining the nature of the role that the first variable plays in achieving the second variable, and this is done by reviewing the reality of tourism investment in the state of Chlef while trying to determine the degree of its impact on the stimulation of tourism movement in the state. the state. To answer the main problem and test the validity of the proposed hypotheses, the deductive method was used with its tools of description and analysis. Through this study, a number of results were reached, the most important of which is that tourism investment has a major role in stimulating the tourism movement in the state of Chlef, provided that this investment includes the various tourism components that the state harnesses, and it must be well planned.